(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A Greenhouse is a framed structure that is used for the production of fruits, vegetables, flowers, and any other plants that require special conditions of temperature and humidity. Greenhouses warm up during the day-times when sun-rays penetrate through them, which heat the plant, soil and the structure. The greenhouse effect is a natural phenomenon and is very beneficial to the human being. With lack of proper green house monitoring and control system the production decline which leads to loss.There are many challenges starting from plant growth to maintenance for which monitoring and control of greenhouse is needed. This paper explains the design and implementation of a network with wireless sensors for greenhouse environment monitoring and controlling. This greenhouse control system is controlled by Raspberry pi with its wifi capability that is attached to a temperature sensor, soil moisture sensor, Light Dependent Resistor (LDR) sensor, 12V DC fan and pump. With the monitoring and control of greenhouse the performance of the system and production can be increased. A prototype was designed and builtup whose results were presented.